PROFIL SENSORI DESKRIPTIF PRODUK PEMANIS TUNGGAL DAN CAMPURAN - Dede Robiatul Adawiyah; Dian Puspitasari; Lince Lince (Jurnal Teknologi dan Industri Pangan, 2020)
Sweetener as a food additive which gives sweet taste has a different profile from sucrose. Intensity profile and attribute sensation become very useful in developing mixed sweeteners from single sweeteners to create commercial sweeteners having a sucrose-like profile. However, there is only few data of attribute intensity and descriptive profiles of single sweeteners. The aim of this research was to analyze the des-criptive profile of single and mixed sweeteners using quantitative descriptive analysis (QDA), time intensity (TI), and temporal dominance of sensations (TDS) methods. The results of QDA descriptive profile showed that samples of a single sweetener T3 as well as mixed sweetener containing C2 and C5 had the same characteristics as sucrose. The results of TI descriptive profiles showed that the time intensity curves of sweet attribute of a sample of two mixed sweeteners C1 and C2, and a single sweetener T3 were similar to that of sucrose. The results of the descriptive profile using TDS methods generally showed that the do-minant attributes of all samples were sweet, sweet aftertaste, and licorice. Bitter and bitter aftertaste attri-butes were found in single sweetener T7, while mixed sweetener C1 had best sensory characteristics than the others.